Penerapan Konsep Green Infrastructure sebagai Upaya Pengendalian Banjir pada Sub DAS Citepus - Farhan Rizky Mahardika; Hilwati Hindersah (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. Flood is a condition where there is an increase in the volume of water on a land surface. This is because the capacity of a water body is not able to accommodate the increased water runoff. The Citepus sub-watershed is one of the watersheds located in the Bandung City and empties into Dayeuhkolot District, Bandung Regency. The existing condition of the watershed which has an area of ​​21.92 km² is surrounded by residential which causes a decrease in regional air absorption, resulting in frequent flooding in the Citepus sub-watershed. And then, with the results of the analysis on the WebGIS which shows that Citepus sub-watershed has 48 flood-prone point. Therefore, there is a need for flood control efforts with the concept of spatial planning needed for the development of green infrastructure. Based on the problems above, the purpose of this research is to apply the concept of Green Infrastructure in an effort to control flooding in the Citepus sub-watershed. The methodology of this research is descriptive research with a deductive approach. Meanwhile, the analytical methods used are superimpose analysis, select analysis based on attributes in ArcGIS software, and hydrological analysis. Based on the analysis that has been carried out, it can be seen that there are two types of green infrastructure, namely detention and bioretention ponds, which are suitable to be applied to the Citepus sub-watershed. The application of detention ponds in the Citepus sub-watershed with an area of ​​89,144 ha, can reduce the potential for flooding in the Citepus sub-watershed by as much as 10%. Meanwhile, for the application of bioretention in the Citepus sub-watershed with an area of ​​10,353 ha, it can reduce the potential for flooding in the Citepus sub-watershed by 1.15%. Abstrak. Banjir adalah suatu kondisi dimana terjadinya peningkatan volume air pada suatu permukaan tanah. Hal tersebut dikarenakan kapasitas dari suatu badan air tidak mampu menampung limpasan air yang meningkat. Sub DAS Citepus merupakan salah satu daerah aliran sungai yang berada di Kota Bandung dan bermuara di Kecamatan Dayeuhkolot, Kabupaten Bandung. Kondisi eksisting daerah aliran sungai yang memiliki luas 21,92 km² ini dikelilingi oleh permukiman yang menyebabkan berkurangnya daerah resapan air sehingga berakibat pada terjadinya banjir yang seringkali terjadi pada sub DAS Citepus ini. Hal tersebut diperkuat lagi dengan hasil analisis pada website WebGIS yang menunjukkan bahwa pada sub DAS Citepus memiliki 48 titik rawan banjir. Maka dari itu, perlu adanya upaya pengendalian banjir dengan konsep penataan ruang yang mengedepankan pembangunan infrastruktur hijau. Berdasarkan permasalahan di atas, maka tujuan dari penelitian ini adalah menerapkan konsep Infrastruktur Hijau dalam upaya pengendalian banjir pada sub DAS Citepus. Adapun untuk metodologi dari penelitian ini adalah penelitian deskriptif dengan pendekatan deduktif. Sementara itu, untuk metode analisis yang digunakan adalah analisis superimpose, analisis select by attributes pada software ArcGIS, dan analisis hidrologi. Berdasarkan hasil analisis yang telah dilakukan, dapat diketahui bahwa terdapat dua jenis infrastruktur hijau, yakni kolam detensi dan bioretensi, sesuai untuk diterapkan pada sub DAS Citepus. Penerapan kolam detensi pada sub DAS Citepus dengan luas 89,144 ha, dapat mengurangi potensi terjadinya banjir pada sub DAS Citepus sebanyak 10%. Sementara itu untuk penerapan bioretensi pada sub DAS Citepus dengan luas 10,353 ha, dapat mengurangi potensi terjadinya banjir pada sub DAS Citepus sebanyak 1,15%.